Rola czynnika społecznego w procesie stanowienia planu zagospodarowania przestrzennego gminy - Barańska, Marzena (Wydawnictwo Naukowe WNPiD UAM, 2012)
In modern democracies, local residents’ awareness concerning their participation in the decision-making process is becoming increasingly important. The expanding range of instruments provided by existing law enables them to claim their rights not only by means of a system of legal complaints, but to take advantage of the privilege of civil disobedience, and also to become involved in lobbying. This particular aspect of activity has been observed recently, when changes in architectural developments, expansion of motorways, erection of public facilities, and changes of the use of land to serve a different purpose has resulted in the greater public interest sometimes losing priority, at least in the eyes of individual citizens or from the point of view of their interests. Practice is an important factor for citizens to become more and more aware of the opportunities to apply legislative solutions in order to express their approval or disapproval of the changes proposed for a particular location, especially when these concern the immediate neighborhood and are related to residential conditions, development of infrastructure, and investment plans. Experience shows that, as time goes by, we are becoming more involved in the defense of ‘local public interest’. The purpose of this paper is to demonstrate how local communities and individuals take advantage of the privilege of participating in the process of applying legally sanctioned solutions to the establishment of spatial management plans at the district level and what instruments they use most frequently.
The role of social factors in the process of establishing the spatial management plan of a district
Keywords: czynnik społeczny; zagospodarowanie przestrzenne gminy